A comprehensive study on energy meters and power tampering attempts - Shagufta Khan; Manoj saini (International Journal of Applied Power Engineering (IJAPE), 2021)
Electricity is the basic need of today’s scenario. In the 21st generation, growth and development is totally dependent on electricity. Thus, measurement of consumption of electricity becomes much more important. Energy meter used to measure consumed electricity by building or electrical equipment of various end users. This paper focuses on review of energy meters and power tampering attempts. It will highlight the development of meters from electromechanical meters to smart meters. The need of an era is to develop a more reliable and intelligent smart energy meters. This paper also discussed type of power tampering efforts in energy meters for power theft. The concept of smart meters for removing the power tampering efforts is also discussed.